Sustainable development of educational institutions in the context of the introduction of elements of distance education in the learning process - Aitbayeva, B.M.; Maulenova, A.M.; Akhmetzhanova, Z.B.; Kenzhebekova, Z.A.; Rakhimbayeva, B.O. (Periodico Tche Quimica, 2019)
Distance education is essentially the basis for the development of educational institutions that provide innovative services, which cannot be obtained elsewhere. It is believed that distance education is a substitute for the traditional as part of simplifying and cheapening the learning process. At the same time, the leading global trends suggest the need for the development of elements of self-education and the expansion of the geographical nature of educational offers. The relevance of the study is that it is necessary to distinguish between the use of distance education methods in the traditional sphere and the sphere of training professionals. The paper presents the concept of the need to integrate elements of distance education in the process of preparing university teachers. The authors believe that teachers in drawing up courses and applying learning technologies use the same techniques as in distance learning. Therefore, the use of distance learning technologies can be shown as the basis for the development of advanced training programs and additional professional education. The authors proposed a study on the need and sufficiency of the use of distance education technologies and the possibilities for their integration into the process of postgraduate education. The practical significance of the work is determined by the fact that the possibilities of self-development of teachers are fully disclosed, not only as subjects of the educational process but also as subjects of training. © 2019 Tche Quimica Group. All rights reserved.
DESENVOLVIMENTO SUSTENTÁVEL DE INSTITUIÇÕES EDUCACIONAIS NO CONTEXTO DA INTRODUÇÃO DE ELEMENTOS DA EDUCAÇÃO À DISTÂNCIA NO PROCESSO DE APRENDIZAGEM
Keywords: Development; Distance education; Structure; Teacher; Training